1996
DOI: 10.1161/01.str.27.3.435
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Insertion/Deletion Polymorphism and Cerebrovascular Disease

Abstract: Low ACE activity at sroke presentation and possession of the D allele may be associated with increased risk of early death from acute cerebral infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 22 publications
4
84
2
Order By: Relevance
“…118 In clinical-genetic studies, the ACE I/D genotype has been associated with ischemic stroke in hypertensives, 119 the DD genotype with lacunar stroke, 120 and low ACE activity at stroke presentation and the D allele with increased risk of early death from acute cerebral infarction. 121 There has been inconsistent results for angiotensinogen mutations M235T and T174M for ischemic stroke, 122 and there is an association with the B haplotype of the angiotensinogen promotor gene in absence of the wild-type A haplotype as a susceptibility factor for microangiopathy-related cerebral damage. 123 Angiotensin-Converting Enzyme Inhibitors ACE-I were introduced for the treatment of high blood pressure in the United States in the1970s.…”
Section: Renin-angiotensin System and Strokementioning
confidence: 99%
“…118 In clinical-genetic studies, the ACE I/D genotype has been associated with ischemic stroke in hypertensives, 119 the DD genotype with lacunar stroke, 120 and low ACE activity at stroke presentation and the D allele with increased risk of early death from acute cerebral infarction. 121 There has been inconsistent results for angiotensinogen mutations M235T and T174M for ischemic stroke, 122 and there is an association with the B haplotype of the angiotensinogen promotor gene in absence of the wild-type A haplotype as a susceptibility factor for microangiopathy-related cerebral damage. 123 Angiotensin-Converting Enzyme Inhibitors ACE-I were introduced for the treatment of high blood pressure in the United States in the1970s.…”
Section: Renin-angiotensin System and Strokementioning
confidence: 99%
“…A strong association between the DD genotype and the D allele with ischemic stroke (IS) was revealed in a number of studies, [7][8][9][10] while others showed no such association. [11][12][13][14] Siera et al [15] investigated a possible association between 3 different genetic polymorphisms of RAS and the presence of cerebral white matter lesions (WML) in 60 never-treated essential hypertensive patients (36 men, 24 women), aged 50 to 60 years, without clinical evidence of target organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] The previously established difference in levels of plasma ACE activity between BN and LE rats 12 offers the opportunity to study a possible predictive role for the genetically determined basal plasma ACE activity in ICV pathology in the rat. This was investigated in 2 consecutive series of BC(F1XBN) rats.…”
Section: Discussionmentioning
confidence: 99%
“…4 An association between ACE polymorphism and various cardiovascular disorders has been investigated, 5,6 and conflicting results were obtained for the association between ACE gene polymorphism and stroke in humans. [7][8][9][10][11] Different levels of plasma ACE activity have also been demonstrated in various strains of rats and shown to be primarily genetically determined. 12 Indeed, plasma ACE activity levels are higher in the BN rat, which is also prone to intracerebral vascular lesions, than in the LE rat.…”
Section: See Editorial Comment Page 2684mentioning
confidence: 99%